Experimental and Numerical Investigations on a Phase Change Material Based Heat Sink with Symbiotically Joined Heat Pipe - Kumar Marri, Girish; Balaji, Chakravarthy (Heat transfer engineering, 2021)
This paper reports the results of experimental and numerical investigations on a phase change material based heat sink, with a compact heat pipe as the thermal performance enhancer. The evaporator of heat pipe is placed in such a way that, it is in symbiotic association with the phase change material in the heat sink. Visualization studies and numerical simulations are carried out using a digital camera and enthalpy porosity formulation with equivalent thermal conductivity model respectively. Parametric studies are carried out at 33, 66 and 99% fill ratios of phase change material and at power levels of 6, 8 and 10 W. The heat sink with heat pipe shows superior performance at all fill ratios of the phase change material and for all input power levels over the heat sink without the heat pipe. Experiments are also conducted on a heat sink with radial plate fins as an embedded thermal performance enhancer. Results are very encouraging with the heat sink coupled with the heat pipe showing an enhancement up to 30% and 175% in the time to reach set points during charging and discharging cycles respectively, and in overall effectiveness, it shows 3.58 times enhancement over the heat sink with embedded thermal performance enhancers.